2022
DOI: 10.3390/su14052953
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal(loid)s Pollution of Agricultural Soils and Health Risk Assessment of Consuming Soybean and Wheat in a Typical Non-Ferrous Metal Mine Area in Northeast China

Abstract: During mining, some of the essential metal(loid)s for plants or humans are discharged into the environment with non-essential metal(loid)s. Thus, comprehensive investigations of their distribution and the health risk of consuming food crops near mines are significant. A total of 26 soils and 25 food crops (soybean grains and wheat grains) were sampled to investigate arsenic (As), cadmium (Cd), chromium (Cr), copper (Cu), mercury (Hg), lead (Pb), zinc (Zn), selenium (Se), molybdenum (Mo), and manganese (Mn) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
3
1
Order By: Relevance
“…The result is similar to the results reported for market sold beans from Katsina, Nigeria [36]. But the concentrations are lower to values reported in a study in eastern Nigeria [33] and that recorded by Zahir et al [41] in a study conducted in Pakistan and the results for the study conducted by Li et al [29].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The result is similar to the results reported for market sold beans from Katsina, Nigeria [36]. But the concentrations are lower to values reported in a study in eastern Nigeria [33] and that recorded by Zahir et al [41] in a study conducted in Pakistan and the results for the study conducted by Li et al [29].…”
Section: Discussionsupporting
confidence: 89%
“…The recorded Pb concentrations in the study were low when compared to the reported Pb concentration range for soybeans samples from Iran [28] and the reported concentrations for soybean samples from Northeast China [29]. These values are also lower than the WHO safe limit for Pb in Cereals reported in literature [30].…”
Section: Discussioncontrasting
confidence: 66%
“…It makes the dry season from November to March the next year. Another period of the year is the mean flow season [21]. This study divided cultivated land into crop levels to provide a scientific basis and more detailed management suggestions for local agricultural land planning and soil management.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…It makes the dry season from November to March the next year. Another period of the year is the mean flow season [21]. The mainland use of the Hulan River Basin was cultivated land.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…Arsenic in soil can accumulate in crops and migrate into lake water and groundwater, affecting crop yield and also causing serious harm to human health and local ecosystems [ 4 , 5 , 6 ]. When crops absorb excessive amounts of arsenic from the soil, they are subject to arsenic toxicity, which can manifest as inhibited root growth, stunted plant growth and development, and even death, resulting in decreased crop yield and affecting food security [ 7 , 8 , 9 ]. Physiologically, the toxicity of arsenic leads to the accumulation of reactive oxygen species in plant cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%